Image enhancement technique using lifting and stationary wavelet transforms and contrast limited adaptive histogram equalization - V. Hyma Lakshmi, T.; Madhu, T; Ch. Sri Kavya, K. (International Journal of Engineering and Technology, 2019)
This paper presents a new image enhancement technique which includes both resolution enhancement and contrast enhancement. In this proposed method Stationary Wavelet Transform (SWT) is used in combination with Lifting Wavelet Transform (LWT) for resolution enhancement and SWT with the combination of Contrast limited adaptive histogram equalization (CLAHE) for contrast enhancement. SWT is used in combination with LWT improves the resolution and also minimize the execution time drastically than existing methods and SWT is used in combination with CLAHE to enhance the contrast and mitigate the noise effects than existing methods. The proposed method gives superior results than existing techniques and it is proved with PSNR, Noise Estimation and RMSE and visual results.Â Â